2011
DOI: 10.1242/dev.072157
|View full text |Cite
|
Sign up to set email alerts
|

Midkine and Alk signaling in sympathetic neuron proliferation and neuroblastoma predisposition

Abstract: SUMMARYNeuroblastoma (NB) is the most common extracranial solid tumor in childhood and arises from cells of the developing sympathoadrenergic lineage. Activating mutations in the gene encoding the ALK tyrosine kinase receptor predispose for NB. Here, we focus on the normal function of Alk signaling in the control of sympathetic neuron proliferation, as well as on the effects of mutant ALK. Forced expression of wild-type ALK and NB-related constitutively active ALK mutants in cultures of proliferating immature … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
62
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 77 publications
(74 citation statements)
references
References 75 publications
(109 reference statements)
11
62
0
1
Order By: Relevance
“…Interestingly, the ALK gene itself is upregulated in human NB presenting with ALK mutations [29]. Strikingly, this upregulation is also observed in murine MYCN / Alk tumors compared with MYCN tumors and in the ganglia of mutated animals, in agreement with the reported ALK autoregulation [19,33]. Altogether, these data strongly indicate that tumors obtained in our models are fully relevant to human NB.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Interestingly, the ALK gene itself is upregulated in human NB presenting with ALK mutations [29]. Strikingly, this upregulation is also observed in murine MYCN / Alk tumors compared with MYCN tumors and in the ganglia of mutated animals, in agreement with the reported ALK autoregulation [19,33]. Altogether, these data strongly indicate that tumors obtained in our models are fully relevant to human NB.…”
Section: Discussionsupporting
confidence: 85%
“…In vitro , sympathetic neuroblast proliferation has been shown to be increased upon overexpression of wild-type (Wt) ALK as well as R1275Q and F1174L mutant forms in a culture model of chick embryonic neuroblasts [19]. Moreover, it has been recently reported that F1174L ALK may transform murine neural crest progenitor cells [20].…”
Section: Introductionmentioning
confidence: 99%
“…ALK has a key role in early sympathoadrenal development to protect neuroblast growth in utero against nutrient deprivation 37, 38 . Germline and somatic mutations in ALK causing constitutive kinase activation are present in 8–10% of neuroblastoma cases and correlate with poor prognosis 3942 .…”
Section: Neuroblastomamentioning
confidence: 99%
“…ALK has been recently extensively studied as a candidate in the development of new targeted treatments for progressive and resistant NB. ALK is expressed in the developing central and peripheral nervous system during embryogenesis [5], and in the developing sympathoadrenal lineage of the NC, where its signaling may regulate the balance between cell proliferation and differentiation [1, 6, 7]. ALK physiological role in the normal development of the nervous system is not yet fully understood, but ALK having a role in neurogenesis control was demonstrated in Drosophila , zebrafish, and chicken [6, 8, 9].…”
Section: Introductionmentioning
confidence: 99%